A quantile regression approach to trail financial performance of manufacturing firms. Issue 3 (12th September 2019) - Nanda, Swagatika; Panda, Ajaya Kumar
Abstract : Purpose: The purpose of this paper is to track the financial performance of manufacturing firms at different levels of their conditional quantiles. It also analyzes the relevance of revenue and cost channels along with key firm-specific parameters that influence firm's profitability. Design/methodology/approach: The study analyses a sample of 1, 000 manufacturing firms over a study period spanning from 2000 to 2016. It uses both quantile regression and panel ordinary linear square (OLS) models to analyze the financial performance of the firms. Findings: The study finds large scale of heterogeneity among the firms under different quantiles of profitability. Export earnings, firm size, asset turnover and volatility of exchange rate are the decisive determinants of financial performance across all quantiles. Financing assets by current debt is negatively impacting return on assets and return on capital employed of firms from lower quantile whereas profitability is positively impacted if they are financed by long term debt. Debt financing of assets does not make any sense for firms with high quantile of profitability. The study also finds that quantile regression approach is a better method than panel OLS models in the presence of highly heterogeneous and non-normal distributions. Research limitations/implications: This study is limited to the financial performance of manufacturing firms and does not consider service sector which is also equally competitive. However, a sector wise analysis of firm's profitability could be more meaningful than comparing all the firms in one basket of manufacturing domain. Practical implications: The research findings have both practical as well as policy implications. Practically, the study helps the firm managers to identify critical success factors that significantly influence firm's financial performance at different levels of profitability. It also helps the policy makers to align policy focus to stabilize firms at lower level of profitability and also to manage conducive business environment for all firms at different levels of their profitability. Originality/value: The study provides a deep theoretical underpinning of literatures on firm's financial performance and empirically investigates it using advanced methodology. The robust estimates of the study ensure to analyze financial performance under revenue and cost channels at diverse level of their profitability.